Is collaborative management always possible? The case of Sauce Grande River Basin, Argentina. Issue 2 (3rd April 2019) - Zilio, Mariana I.; Seitz, Carina; Scordo, Facundo; Gil, Verónica; Zapperi, Paula; Costilla, Paula; Huamantinco Cisneros, M. Andrea; Perillo, Gerardo M. E.; Piccolo, M. Cintia
ABSTRACT: The continuous interaction between human activities and environment leads to adopting a broad approach for studying watershed systems. Undoubtedly, designing an efficient but also sustainable river-basin management plan requires considering the ecosystem, the economic and social aspects related to the use of natural resources. Given the practical and theoretical relevance that stakeholders' participation has achieved in the frame of new approaches for watershed management, this paper aims to identify the possibility of implementing a collaborative strategy in the particular case of the Sauce Grande River Basin (SGRB), Argentina. Such implementation requires the fulfilment of some key conditions that heighten or hinder their execution. Our results indicate that, although the complexity of the basin makes necessary the implementation of a collaborative plan, it is not plausible in the short term. Some issues, such as the engagement of all stakeholders (inside and outside the basin), and the simplification and coordination of the norms and levels of decision making, should be taken into account for implementing a collaborative management in the basin. Otherwise, the implementation could have a non-expected result on the socio-ecological system, generating an immediate reject to more participative strategies.